Generators and relations for wreath products - Drozd, Yu.A.; Skuratovskii, R.V. (Український математичний журнал, 2008)
Generators and defining relations for wreath products of groups are given. Under a certain condition
(conormality of generators), they are minimal. Наведено твірні та визначальні співвідношення для вінцевих добутків. За деякої умови (конормальність твірних) вони є мінімальними.